A Wor1-Like Transcription Factor Is Essential for Virulence of Cryptococcus neoformans - Paes, Hugo Costa; Derengowski, Lorena da Silveira; Peconick, Luisa Defranco Ferreira; Albuquerque, Patrícia; Pappas, Georgios Joannis; Nicola, André Moraes; Silva, Fabiana Brandão Alves; Vallim, Marcelo Afonso; Alspaugh, J. Andrew; Felipe, Maria Sueli Soares; Fernandes, Larissa (Frontiers in Cellular and Infection Microbiology, 2018)
Gti1/Pac2 transcription factors occur exclusively in fungi and their roles vary accord-ing to species, including regulating morphological transition and virulence, mating and secondary metabolism. Many of these functions are important for fungal pathogenesis. We therefore hypothesized that one of the two proteins of this family in Cryptococcus neoformans, a major pathogen of humans, would also control virulence-associated cel-lular processes. Elimination of this protein in C. neoformans results in reduced poly-saccharide capsule expression and defective cytokinesis and growth at 37 °C. The mu-tant loses virulence in a mouse model of cryptococcal infection and retains only partial virulence in the Galleria mellonella alternative model at 30 °C. We performed RNA-Seq experiments on the mutant and found abolished transcription of genes that, in combination, are known to account for all the observed phenotypes. The protein has been named Required for cytokinesis and virulence 1 (Rcv1).